2020
DOI: 10.20944/preprints202008.0696.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Reaches the Human Nervous System: How?

Abstract: Without protective and/or therapeutic agents the SARS-CoV-2 infection known as coronavirus disease 2019 (COVID-19) is quickly spreading worldwide. It has surprising transmissibility potential, since it could infect all ages, gender, and human sectors. It attacks respiratory, gastrointestinal, urinary, hepatic, and endovascular systems and can reach the peripheral nervous system (PNS) and central nervous system (CNS) through known and unknown mechanisms. The reports on the neurological manifestations and compli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 228 publications
(375 reference statements)
0
3
0
Order By: Relevance
“…Often, MDCSs are absent or redundant under steady-state physiological conditions (He et al, 2018). The body functions of patients infected with COVID-19 orchestration are disordered, and these changes exponentially increase with the patient's age (Uversky et al, 2020a). Overall, the cluster of gene expression matrixes in the leukocytes revealed that 12 and 5 clusters are dominated in COVID-19 patient and healthy control, respectively.…”
Section: Host Immune System Modulation Action Of Lactoferrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, MDCSs are absent or redundant under steady-state physiological conditions (He et al, 2018). The body functions of patients infected with COVID-19 orchestration are disordered, and these changes exponentially increase with the patient's age (Uversky et al, 2020a). Overall, the cluster of gene expression matrixes in the leukocytes revealed that 12 and 5 clusters are dominated in COVID-19 patient and healthy control, respectively.…”
Section: Host Immune System Modulation Action Of Lactoferrinmentioning
confidence: 99%
“…The virus reached almost all countries, infected humans of all ages, and even affected many animals (Uversky et al, 2020b). The virus reaches almost all human organs, including the central and peripheral nervous systems Uversky et al, 2020a), and has unexpected vertical and horizontal infectivity potential (Elrashdy et al, 2020; LF action against SARS-CoV-2, on comparison of the human and animal LFs, and on determining whether the milk whey action against SARS-CoV-2 depends on LF alone or on other milk ingredients, such as human milk oligosaccharides (HMOs) and/or short-chain fatty acids. Our report fills these gaps and produces an overview of the field, providing answers to some fundamental questions, such as why breastfed children are mostly unaffected by COVID-19 (Fan et al, 2020;Liu et al, 2021;Mitoulas, Schärer-Hernández & Liabat, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the olfactory route (olfactory receptor neurons (OSNs) of the olfactory epithelium, olfactory bulb, and glomeruli, and their projections), which are used by neurotropic CoVs to transmit from the upper respiratory tract into the CNS, three other probable pathways have also been recognized that help these CoVs to reach the CNS from the periphery, which are as follows: (1) Neurotropic CoVs in the lower respiratory tract infect monocytes, neutrophils, lymphocytes, and macrophages of the alveoli capillaries and then spread via hematogenous transmission to get the BBB. They cross it through diapedesis and then infect neuronal and glial cells (Alquisiras-Burgos et al 2020;Uversky et al 2020); (2) Respiratory CoVs can also reach the CNS via retrograde neuronal dissemination. In fact, neurotropic CoVs firstly infect PNS, and following peripheral nerve infection, they access the CNS by axonal transport systems (Koyuncu et al 2013).…”
Section: Neuro-infection With Sars-cov-2 In Animalsmentioning
confidence: 99%